COMPARISON OF THE EFFECTIVENESS OF SOCIAL ASSISTANCE ZAKAT ON POVERTY ALLEVIATIAN IN INDONESIA - Fridyani, Frini; Kurnia, Tuti (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to determine the comparison of the effectiveness of social assistance and zakat on poverty alleviation in Indonesia. This research method uses quantitative methods with secondary data collection methods. The data analysis technique used is Panel Data Regression. The analysis results show that the regression model used is feasible to explain the independent variables, indicated by a significant F-statistic value (p < 0.05). This has a significant effect on the dependent variable. Partially, some independent variables show a significant influence on the dependent variable, namely the number of social assistance recipients, the number of consumptive social assistance programs, and the number of consumptive zakat programs. Then the final result shows partially, zakat is proven to be more effective than social assistance in reducing poverty severity.